Republic of the Philippines Public Financial Management and Accountability Assessment : PFM Strategy Implementation Support - World Bank Group (World Bank, Washington, DC, 2016)
This Public Expenditure and Financial Accountability (PEFA) performance assessment report evaluates the seven core pillars of the public financial management (PFM) system of the Government of the Philippines (Government) as set out in the summary assessment below. It evaluates how effectively the PFM system achieves the desirable budget outcomes of aggregate fiscal discipline, strategic allocation of resources, and efficient service delivery. The assessment was conducted through consultations between departmental staff and a World Bank cross-sectoral team, and was managed by a high-level Government steering committee. Where there are PFM weaknesses, the report provides information on areas that reform activity should address more strongly.The recent assessment uses an upgraded 2016 PEFA framework that includes four new indicators on management of assets and liabilities, refines some of the previous indicators, and introduces a stronger focus on internal financial controls. The main report is structured as follows: Chapter one is an introduction explaining the context, purpose and process of preparing the report, specifying the institutional coverage; Chapter two provides an overview of relevant country-related information that provides the context underpinning the indicator results and the overall PFM performance; Chapter three provides the detailed assessment of performance in terms of the seven pillars of the PFM system. It provides analysis and measurement of results in terms of the 31 performance indicators (PIs) of PFM performance; Chapter four includes an integrated crosscutting analysis on performance of the PFM systems and how it impacts on the Government’s ability to deliver on the intended fiscal and budgetary outcomes, and to identify the most important systems weaknesses in that respect; Chapter five provides an overview of government initiatives to improve PFM performance summarizing the approach to PFM reform, including the institutional factors that are likely to impact the planning and implementation of reforms. Annexes 1-4 provide supporting data and information to the assessment; and Annex 5 provides scores assessed using the 2005/2011 PEFA assessment framework for direct comparison with the previous PEFA assessment baseline scores.